2011
DOI: 10.1111/j.1365-2109.2011.02798.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes in the hepatopancreas of Penaeus monodon Fabricius 1798 given aflatoxin B1 diets

Abstract: Fungal contamination of shrimp feeds a¡ects the shelf life leading to substantial economic losses. Ultrastructural changes in Penaeus monodon sub-adults fed three di¡erent doses (50, 1000 and 2000 ppb) of a£atoxin B 1 (AFB 1 ) were studied. At the end of 4 and 8 weeks of experiment, the hepatopancreas of shrimps were observed for ultrastructural changes. The prominent ultrastructural changes in hepatopancreas of the shrimps fed 1000 and 2000 ppb AFB 1 were rupture of cell membrane and microvillus border, damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
11
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
8
11
0
3
Order By: Relevance
“…The modifications in B-cell and mitotic E-cell activity observed in the present study are consistent with those previously reported for P. monodon fed diets contaminated with pure aflatoxin B1 (Gopinath and Raj 2009), affecting the normal function of absorption and storage of nutrients due to a reduced number of R-cells, production of digestive enzymes by F-cells, and secretion of enzymes by B-cells, culminating in the disruption of the digestive, metabolic, and detoxification functions of the hepatopancreas. Lightner et al (1982) and Bautista et al (1994) observed a significant reduction of lipid vacuoles in Litopenaeus stylirostris receiving 20 g kg -1 pure aflatoxin B1 by injection and P. monodon fed diets containing pure aflatoxin B1.…”
Section: B-cell Activity Mitotic E-cell Activity and Lipid Vacuolessupporting
confidence: 95%
See 1 more Smart Citation
“…The modifications in B-cell and mitotic E-cell activity observed in the present study are consistent with those previously reported for P. monodon fed diets contaminated with pure aflatoxin B1 (Gopinath and Raj 2009), affecting the normal function of absorption and storage of nutrients due to a reduced number of R-cells, production of digestive enzymes by F-cells, and secretion of enzymes by B-cells, culminating in the disruption of the digestive, metabolic, and detoxification functions of the hepatopancreas. Lightner et al (1982) and Bautista et al (1994) observed a significant reduction of lipid vacuoles in Litopenaeus stylirostris receiving 20 g kg -1 pure aflatoxin B1 by injection and P. monodon fed diets containing pure aflatoxin B1.…”
Section: B-cell Activity Mitotic E-cell Activity and Lipid Vacuolessupporting
confidence: 95%
“…Mycotoxins are secondary metabolites produced by different species of fungi, especially of Aspergillus, Penicillium, Fusarium, and Alternaria (Kabak et al 2006), and may be found in food in a conjugated form (Berthiller et al 2009). A considerable reduction in feed intake, weight gain, and survival, as well as necrosis of the hepatopancreas (Boonyaratpalin et al 2001, Soonngam and Hutacharoen 2007, Gopinath and Raj 2009 have been observed in shrimp receiving the pure form of aflatoxin B1, either injected or added to the diet. It has been shown that naturally contaminated feeds are more toxic than feeds containing a similar concentration of pure mycotoxin (Applebaum et al 1982, Foster et al 1986 due to the additive, synergistic, potentiative or antagonistic effect caused by the presence of other mycotoxins (Klaasen and Eaton 1991).…”
Section: Introductionmentioning
confidence: 97%
“…(KLICH, 2007). Alimentos para animais aquáti-cos contaminados com AFs podem causar anormalidades que resultam na queda da produtividade do cultivo (GOPINATH et al, 2012). A tilápia do Nilo (Oreochromis niloticus), principal espécie de peixe cultivada no Brasil (BRASIL, 2010), é sensível à contaminação por AFs, caracterizada pela ocorrência de quadros de caquexia, despigmentação das escamas, icterícia e lesões hepáticas, responsáveis por gerar prejuízos econômi-cos em seu cultivo (KUBITZA, 2010).…”
Section: Introductionunclassified
“…When consuming aflatoxin B1 contaminated food, Litopenaeus vannamei and Penaeus stylirostris presented lesions in the hepatopancrea, antennal gland, mandible organ and hematopoietic organs (BINTVIHOK et al, 2003). Levels of 1000 ng / g of aflatoxin B1 also reduces shrimp growth; decreases blood cells, making shrimp more vulnerable to pathogens; causes decrease in lipid deposit by the hepatopancrea cells and reduction of the survival rate (BOONYARATPALIN et al, 2001;GOPINATH & RAJ, 2009, GOPINATH et al, 2012. The objective of this research was to quantify and identify the toxigenic mycobiota and aflatoxins occurrence in feed intended for shrimp cultivated in the coastal area of Piauí, Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…These toxicants are particularly important in aquaculture since their presence exerts a negative economic impact on relevant commerce as well as severe health problems after exposure to infected food and feed. Toxic feed contaminants can cause abnormalities such as poor growth, physiological imbalances and histological changes that result in yield reduction and profitability of shrimp culture (GOPINATH, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%